Arabic Learning Curriculum Based on Santri Adaptation in the Era of Society 5.0: Concepts and Implications: Kurikulum Pembelajaran Bahasa Arab Berbasis Adaptasi Santri di Era Society 5.0 : Konsep dan Implikasi (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2022)
Society 5.0 gives a new nuance to learning Arabic. Optimizing the use of cyber as a learning medium adds to the attractiveness of santri in learning Arabic. The purpose of this study is to determine the concepts and implications of the Arabic language learning curriculum based on the adaptation of students in the era of society 5.0. This research is library research that collects secondary data from various kinds of literature such as books, journal articles, and information from relevant official websites. The data that has been collected will be clasificated, followed by an in-depth discussion. The result of this research is that the Arabic language learning curriculum based on the adoption of santri in the era of society 5.0 combines the pesantren curriculum and other appropriate modern curriculum. It utilizes the latest technology as a media for Arabic learning.
Keywords: Curriculum, Santri, Arabic Learning, Society 5.0